2020
DOI: 10.7171/jbt.20-3102-001
|View full text |Cite
|
Sign up to set email alerts
|

Multisite Evaluation of Next-Generation Methods for Small RNA Quantification

Abstract: Small RNAs (smRNAs) are important regulators of many biologic processes and are now most frequently characterized using Illumina sequencing. However, although standard RNA sequencing library preparation has become routine in most sequencing facilities, smRNA sequencing library preparation has historically been challenging because of high input requirements, laborious protocols involving gel purifications, inability to automate, and a lack of benchmarking standards. Additionally, studies have suggested that man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 13 publications
2
17
1
Order By: Relevance
“…A direct comparison of AQRNA-seq to six commercial small RNA-seq kits ( Fig. 2d ), 27 as well as additional reports using the miRXplore reference, 5 , 21 , 28 established AQRNA-seq as the most quantitatively accurate RNA-seq workflow.…”
Section: Resultsmentioning
confidence: 88%
“…A direct comparison of AQRNA-seq to six commercial small RNA-seq kits ( Fig. 2d ), 27 as well as additional reports using the miRXplore reference, 5 , 21 , 28 established AQRNA-seq as the most quantitatively accurate RNA-seq workflow.…”
Section: Resultsmentioning
confidence: 88%
“…In addition, EdgeSeq, a platform using hybridization probes and targeted sequencing readout, speci cally designed for ease-of-use in clinical setting, is available as an alternative to small RNA-Seq. Previous comparative studies performed on a subsets of available methods revealed vast di erences in their performance (7,(9)(10)(11)(12)(13)(14)(15)(16)(17). However, how current commercial small RNA-Seq methods perform, particularly in challenging setting such as liquid biopsy samples, is not yet established.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, high-throughput assays for DNA and RNA extraction have been adopted in the recently updated molecular testing guidelines for the selection of patients with lung cancer for treatment with targeted tyrosine kinase inhibitors, jointly supported by the College of American Pathologists, the International Association for the Study of Lung Cancer, and the Association for Molecular Pathology [29]. However, considering the critical consequences that the analysis of cytological samples may have for patients in terms of diagnosis, prognosis, disease monitoring, and treatment outcomes, we strongly recommend that the implementation of molecular testing as a standard-of-care be performed only after in-house validation, considerations regarding the bias of expression level normalization [30, 31], and under very strict technical QCs, such as those developed for other high-throughput tools [31-36].…”
Section: Discussion/conclusionmentioning
confidence: 99%